2007
DOI: 10.3892/or.17.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-cryptoxanthin inhibits N-butyl-N-(4-hydroxybutyl)nitrosamine-induced urinary bladder carcinogenesis in male ICR mice

Abstract: Abstract. Recent epidemiological studies have indicated that high dietary consumption of fruit and vegetables results in lower risk of bladder cancer. To confirm these findings, we investigated in the current study the effects of dietary administration with ß-cryptoxanthin extracted from Citras unshiu oranges on N-butyl-N-(4-hydroxybutyl)nitrosamine (OH-BBN)-induced urinary bladder carcinogenesis in mice. Male ICR mice were divided into 6 experimental and control groups. Groups 1 through 4 were given OH-BBN (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…b-Cryptoxanthin-supplemented ICR mice had a decreased incidence of preneoplastic and neoplastic lesions of the urinary bladder. 123 Furthermore, in a study in which F344 rats were provided varying doses of b-cryptoxanthin, the high-dose (25 ppm) group showed a decreased incidence of colon cancer. 124 Thus, besides evidence that b-cryptoxanthin may be involved in functions associated with cancer prevention, there is also some evidence linking moderate intakes of b-cryptoxanthin with cancer-preventive effects.…”
Section: B-cryptoxanthin As a Cancer Preventivementioning
confidence: 99%
“…b-Cryptoxanthin-supplemented ICR mice had a decreased incidence of preneoplastic and neoplastic lesions of the urinary bladder. 123 Furthermore, in a study in which F344 rats were provided varying doses of b-cryptoxanthin, the high-dose (25 ppm) group showed a decreased incidence of colon cancer. 124 Thus, besides evidence that b-cryptoxanthin may be involved in functions associated with cancer prevention, there is also some evidence linking moderate intakes of b-cryptoxanthin with cancer-preventive effects.…”
Section: B-cryptoxanthin As a Cancer Preventivementioning
confidence: 99%
“…Carotenoid is also a matter of great interest. Astaxanthine [9 ] and cryptoxanthine [10] have gained special interest. Some papers have reported the synergy resulting from carotene-tocopherol interactions [11] and also that observed for a mixture of various carotenes [12].…”
Section: Basic Science On Nonnutritive Functional Food Componentsmentioning
confidence: 99%
“…As with other carotenoids, b-Crp acts as an antioxidant and scavenges radicals (Miller, Sampson, Candeias, Bramley, & Rice-Evans, 1996) and stimulates the repair of oxidative damage to DNA (Lorenzo et al, 2009). Other studies have indicated that b-Crp reduces the risk of lung and colon cancers (Lian, Hu, Russell, & Wang, 2006;Miyazawa et al, 2007;Tanaka et al, 2000;Yuan, Stram, Arakawa, Lee, & Yu, 2003) and postmenopausal osteoporosis (Yamaguchi, 2008), suggesting that b-Crp has a wide range of beneficial functions in the body. However, effects of b-Crp on the immune system have not currently been investigated.…”
Section: Introductionmentioning
confidence: 96%